2014
DOI: 10.1371/journal.pone.0103206
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 Is Overexpressed in Cutaneous Squamous Cell Carcinoma and Regulates Cell Motility and Colony Formation Ability of Tumor Cells

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a malignancy of epidermal keratinocytes that is responsible for approximately 20% of skin cancer-related death yearly. We have previously compared the microRNA (miRNA) expression profile of cSCC to healthy skin and found the dysregulation of miRNAs in human cSCC. In this study we show that miR-31 is overexpressed in cSCC (n = 68) compared to healthy skin (n = 34) and precancerous skin lesions (actinic keratosis, n = 12). LNA in situ hybridization revealed that miR-31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
(29 reference statements)
4
43
0
Order By: Relevance
“…Another study demonstrated that miR-365 promoted cSCC tumor formation by directly targeting NFIB [30]. MiR-31 also overexpressed in cSCC and it enhances cell migration and invasion capacity of cSCC cells [31]. In this study, we found the miR-199a-5p expression levels were significantly decreased in cSCC cells and cSCC tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Another study demonstrated that miR-365 promoted cSCC tumor formation by directly targeting NFIB [30]. MiR-31 also overexpressed in cSCC and it enhances cell migration and invasion capacity of cSCC cells [31]. In this study, we found the miR-199a-5p expression levels were significantly decreased in cSCC cells and cSCC tissues.…”
Section: Discussionsupporting
confidence: 51%
“…These data support the idea that miR‐31 may play a crucial role in the biology of rodent hair follicles. miR‐31 is also upregulated in skin diseases such as psoriasis and squamous cell carcinoma (SCC), indicating that miR‐31 plays a role in the response to restoring epidermal homeostasis or driving hyperproliferation . Interestingly, in other cell types miR‐31 can inhibit proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA‐31 expression was higher in cSCC than healthy skin and precancerous skin lesions . In addition, miR‐31 was specifically up‐regulated in cSCC cancer cells.…”
Section: Deregulated Micrornas In Csccmentioning
confidence: 95%